„Ein junges, neues Geschlecht wird besseres liefern als das alte“. Ein Empfehlungsbrief Alexander von Humboldts für Carl Ludwig - Ette, Ottmar; Schwarz, Ingo (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2024)
Abstract:A letter from Alexander von Humboldt to a minister in the liberal government of the Electorate of Hesse is published here for the first time. In this letter from 1849, Humboldt praised the achievements of a young professor at the University of Marburg: Carl Ludwig, now famous for his groundbreaking discoveries in physiology. Humboldt’s friend and colleague, Emil du Bois-Reymond, had facilitated the contact between Ludwig and Humboldt. The letter of recommendation, with which Humboldt sought to help improve Ludwig’s financial situation, is an example of how Humboldt promoted the work of young scientists and independent scientific institutions.